Magnetic measurements of the 63-pole 2 Tesla superconducting wiggler for Canadian light source - Bekhtenev, E.A.; Kuzin, M.V.; Khruschev, S.V.; Mezentsev, N.A.; Miginsky, E.G.; Shkaruba, V.A.; Tsukanov, V.M. (Вопросы атомной науки и техники, 2006)
The magnet measurement methods for a multipole superconducting wiggler using the Hall probes and stretched wire are described. The results of magnet measurements for the 63-pole superconducting wiggler are presented. The measurements have been carried out in the bath cryostat (with the Hall probes temperature 4.2 K) as well as in its own cryostat using a special scanning room temperature antechamber.